Teachers and Parents Perspective: Is It Difficult for Project-Based Learning (PjBL) During the Covid-19 Pandemic? - Rati, Ni Wayan; Rediani, Ni Nyoman (International Journal of Elementary Education, 2021)
PjBL learning is one of the innovative learning models developed with a constructivist approach, where the learning process provides opportunities for students to be more active in the learning process. The purpose of this study was to identify the obstacles faced by teachers and parents in implementing the PjBL model in the network during the Covid-19 pandemic. The type of research conducted is descriptive qualitative. The sample of this research is 68 teachers and 390 students' parents. data collection methods used are interviews and questionnaires. Before using the instrument, the validity of the instrument was analyzed using the CVR, it was obtained that the CVR value for the teacher constraint questionnaire, the VCR results showed that the 38 instruments developed were valid with a score of 0.73-1. Meanwhile, for the reliability test, the Cronbach Alpha coefficient of 0.82 was obtained. Meanwhile, for parental instruments, CVR showed that the 25 instruments developed were valid with a score of 1 reliability with Cronbach's Alpha, obtained a score of 0.93. Analysis of the data used is the analysis of the data in the study carried out interactively. The results of the analysis show that the constraints are constraints on making learning plans, the availability of learning tools, the availability of tools and materials used in the PjBL learning process, constraints on the participation of other parties in the PjBL learning process, obstacles in the implementation of PjBL learning, especially the implementation of PjBL syntax and the last obstacle. is the PjBL assessment process. As well as the obstacles faced by parents in assisting students to learn, among others, are some parents still have problems providing facilities even though the numbers are not too large, another obstacle faced is that parents experience problems if the tools and materials used in PjBL learning are difficult to obtain, besides that, the obstacles experienced are that parents have difficulty because they do not understand the material being studied by students.